2017
DOI: 10.3390/su9111926
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption and Implementation of Transdisciplinary Research in the Field of Land-Use Science—A Comparative Case Study

Abstract: Transdisciplinary research (TDR) is discussed as a promising approach in land-use science and spatial research to address complex multifaceted "real-world problems" and to design strategies and solutions for sustainable development. TDR has become a widespread research approach in sustainability science and is increasingly promoted by research programmes and agencies (e.g., Future Earth and Horizon 2020). Against this backdrop, TDR can be considered a (social) innovation in the academic system, which is curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 78 publications
2
51
0
Order By: Relevance
“…On the one hand, the project successfully developed a guiding framework for governance through a mutual learning process; on the other, it was confronted with a range of shortcomings typical for transdisciplinary projects (Lang et al, ; Pohl & Hirsch Hadorn, ; Zscheischler et al, ; for an overview see Mann & Schäfer, ). The four governance challenges that we have identified from the literature helped us to systematically address crucial aspects in the strategy development and have been discussed here with regard to findings from transdisciplinary research.…”
Section: Discussion: Addressing Governance Challenges For Sustainablementioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the project successfully developed a guiding framework for governance through a mutual learning process; on the other, it was confronted with a range of shortcomings typical for transdisciplinary projects (Lang et al, ; Pohl & Hirsch Hadorn, ; Zscheischler et al, ; for an overview see Mann & Schäfer, ). The four governance challenges that we have identified from the literature helped us to systematically address crucial aspects in the strategy development and have been discussed here with regard to findings from transdisciplinary research.…”
Section: Discussion: Addressing Governance Challenges For Sustainablementioning
confidence: 99%
“…The guiding idea of this coproduction approach was that collective engagement between researchers and practitioners should take place as an interactive process in which actors, institutions and biophysical as well as technological system conditions mutually shape each other. As minimum standards for such a transdisciplinary research design, collaborative problem‐framing was required as well as integration of knowledge from different disciplines and research–practice collaboration, as previously identified with regard to sustainable land management (Zscheischler, Rogga, & Busse, , pp. 4–6).…”
Section: Methodsmentioning
confidence: 99%
“…Incorporating the natural and social sciences to solve global environmental issues [10], Future Earth has "pioneered approaches to the co-design and co-production of solutions-oriented, transdisciplinary research for global sustainable development" [11].However, transdisciplinary research remains hampered in a number of ways. First, the most recent reviews of transdisciplinary case studies have concluded that the methods and concepts of co-design and co-production processes lack clarity [1,2,4,12]. Second, the majority of extant transdisciplinary research only describes the early stages of co-design, rather than its actual implementation and application [2,7].…”
mentioning
confidence: 99%
“…Second, the majority of extant transdisciplinary research only describes the early stages of co-design, rather than its actual implementation and application [2,7]. Indeed, which studies include key components of early co-design-such as the "framing of problems" [4,12,13], "social capital and partnerships with mutual trust" [14-16], "scaling" [17], "accountability" [9,18], "ownership" [18], as well as "priorities and needs" [1,9]-few have used case studies to discuss both co-design and co-production in a comprehensive, bottom-up manner [4]. Third, in comparison to Europe and North America, markedly few transdisciplinary case studies have been conducted in low-middle income countries in Asia-particularly in terms of health issues [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation